Analisis Kesesuaian Taksiran Berat Janin (TBJ) menggunakan Rumus Johnson- Toshack dengan Berat Badan Bayi Lahir di PMB Nani Suryanti Kota Palembang - Fristika, Yessy Octa; Rosdiana, Meta (NHM PRESS, 2024)
Fetal weight estimation is one way to interpret the weight of the fetus while it is still in the uterus. Fetal weight has a very important meaning in providing midwifery care, especially delivery care. If you know the weight of the fetus to be born, the midwife can determine the time of referral, so that there is no delay in treatment. A very small or very large baby's weight is associated with increased complications during labor and the postpartum period. In addition, by knowing the estimated weight of the fetus, birth attendants can decide whether to plan a spontaneous vaginal birth or not. This study aims to look at the analysis of the suitability of estimated fetal weight (TBJ) using the Johnson-Toshack formula with the birth weight of babies at PMB Nani Suryanti, Palembang City in 2023. This research uses a quantitative descriptive design using secondary data carried out using a cross sectional approach. The research sample was taken by total sampling. The number of samples in this research was 22 samples. There is a significant relationship between the suitability of estimated fetal weight (TBJ) using the Johnson-Toshack formula and the baby's birth weight, namely P-Value = 0.008. The results of this study recommend that other researchers who intend to conduct research on the Appropriateness of Estimated Fetal Weight (TBJ) using the Johnson-Toshack Formula with Birth Weight of the Infant to involve more samples and variables studied with different designs and use instruments that already have value. standard validity and reliability.